2014
DOI: 10.1017/s0022215114000425
|View full text |Cite
|
Sign up to set email alerts
|

Should elective neck dissection be routinely performed in patients undergoing salvage total laryngectomy?

Abstract: Pre-operative neck staging had a negative predictive value of 96 per cent. Given the increased complications associated with neck dissection in the salvage setting, consideration should be given to conservative management of the neck in clinically node-negative patients (staged following primary radiotherapy or chemoradiotherapy).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 39 publications
2
41
0
Order By: Relevance
“…The role of elective neck dissection during STL remains unclear. Although some authors have illustrated improved survival outcomes with elective neck dissection, others have demonstrated no benefit . In our cohort, the rate of occult nodal disease among patients who underwent neck dissection in the absence of preoperative clinically evident nodal burden was 5%.…”
Section: Discussionmentioning
confidence: 52%
“…The role of elective neck dissection during STL remains unclear. Although some authors have illustrated improved survival outcomes with elective neck dissection, others have demonstrated no benefit . In our cohort, the rate of occult nodal disease among patients who underwent neck dissection in the absence of preoperative clinically evident nodal burden was 5%.…”
Section: Discussionmentioning
confidence: 52%
“…We next compared our findings with other studies documenting occult nodal rates in salvage laryngectomy patients 718 . Overall, 11 studies were identified, with a total of 537 patients.…”
Section: Resultsmentioning
confidence: 95%
“…The laryngeal subsite of recurrence was documented in 6 studies (290/1141, 25.4% of patients) that contained patients who were cN0 and received END (164 glottic, 81 supraglottic, 43 transglottic, 2 subglottic). Unilateral and/or bilateral ND was noted in 7 studies . The treatment categories are summarized in Table .…”
Section: Resultsmentioning
confidence: 99%
“…A total of 17 studies met the inclusion criteria and were included in the quantitative metaanalysis. 4,[12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] The 45 excluded studies are summarized in Supporting Information Table S4 with reasons for exclusion.…”
Section: Literature Search Resultsmentioning
confidence: 99%